Network Topology of People NEWS - Mohd Asrah, Norhaidah; Mohd Salleh, Rohayu; Zulkifli, Noor Amiza (Journal of Science and Technology, 2017)
The new method in a survey on public opinion called People NEWS will be highlighted. The application of NEWS which stand for needs, expectations, wants and satisfaction will be highlighted in the process of air travel in Malaysia. The passengerâ€™s opinions according to their NEWS from the first stage process at the departure airport until the final process at the arrival airport will be discussed based on their network topology. The information from the NEWS network can be filtered by using the minimal spanning tree and the description about the behaviour of the network can be explained by using centrality measures.Â Some important results and recommendations based on passengerâ€™s NEWS for Malaysian commercial flights will be highlighted.